An expedient route to highly diversified [1, 2, 3]triazolo[1, 5-a][1, 4]benzodiazepines and their evaluation for antimicrobial, antiproliferative and in silico studies1. Issue 81 (3rd September 2015) - Sudhapriya, N.; Nandakumar, A.; Arun, Y.; Perumal, P. T.; Balachandran, C.; Emi, Nobuhiko
<x xml:space="preserve">Abstract</x> A simple and facile synthesis of a series of diversified [1, 2, 3]triazolo[1, 5-a][1, 4]benzodiazepines has been achieved successfully via a one-pot method under milder conditions and evaluated for their biological activity.